Advances in nanosensors for biological and environmental analysis - Deep, Akash; Kumar, Sandeep (Elsevier, 2019)
Advances in Nanosensors for Biological and Environmental Analysis presents the current state-of-art in nanosensors for biological and environmental analysis, also covering commercial aspects. Broadly, the book provides detailed information on the emergence of different types of nanomaterials as transduction platforms used in the development of nanosensors. These include carbon nanotubes, graphene, 2-D transition metal dichalcogenides, conducting polymers and metal organic frameworks. Additional topics include sections on the way nanosensors have inspired new product development in various types of biological and environmental applications that are currently available and on the horizon.